All I Have Learned, I Have Learned from Google: Why Today's Facial Rejuvenation Patients are Prone to Misinformation, and the Steps We can take to Contend with Unreliable Information - Mehta, Neil; Gupta, Amar; Nissan, Michael (Facial Plastic Surgery, 2019)
A growing number of patients are seeking answers for their health concerns online. This study assesses the reliability, quality, and readability of online materials patients have access to through the Internet and evaluates the social media presence of information providers. An online search was conducted for facial rejuvenation by utilizing three ubiquitously used web search engines: Google, Bing, and Yahoo. The first 25 result pages were collected from each search engine, and exclusionary criteria were applied to exclude online stores and advertisements. Website reliability and quality were assessed via the DISCERN method. Readability was measured through six measurements: Flesch–Kincaid Grade Level (FKGL), Gunning Fox score, SMOG index, Coleman Liau index, and automated readability index. Social media presence and profile followers on Facebook, Twitter, and Instagram were determined to gauge social media presence. Exclusionary criteria yielded 41 unique websites, with the majority of websites authored by physicians (54%) followed by professional organizations (19%). The DISCERN method demonstrated that journal websites yielded the highest overall quality (4.00) and physician websites yielded the lowest (2.72). Readability analysis demonstrated that online forums proved the most challenging to read, and encyclopedia articles were the least challenging. Physician websites maintained the highest social media presence (95%) followed by professional organizations (75%). However, professional organizations had more social media followers in comparison to physician websites. Physician websites and professional organizations overwhelmingly command social media presence compared to other information providers and provide information with serious deficits in reliability and quality. A strong majority of online information also surpasses the health care literacy of patients. This poses a serious concern for physicians who need to provide and guide patients to high quality and reliable information.
Keywords: facial rejuvenation; DISCERN; patient education; online health; information